Secondary attack rate of COVID-19: analysis of contacts of COVID-19 cases admitted in a tertiary care centre, Northern district of Kerala, India-a cross-sectional study - Saraswathy, Anitha S.; Sanya, Rameela; Kumaran, Jayasree A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Secondary attack rate is the proportion of primary contacts that develop infection or symptom within one incubation period after contact with an index case. The secondary attack rate will help in studying and understanding the transmission dynamics of infectious diseases. As coronavirus disease (COVID-19) is a novel disease which has resulted in a pandemic, understanding the transmission dynamics is very important for strengthening preventive measures. Methods: The present cross-sectional study was conducted to estimate the secondary attack rate among primary contacts of COVID-19 cases admitted in a tertiary care centre in Northern Kerala. Secondary attack rate was calculated as the percentage of primary contacts that tested positive for COVID-19 with RT-PCR test within 14 days of exposure. Results: Secondary attack rate was found to be 5.88%, secondary clinical attack rate 2.35% and secondary infection rate 3.53%. Among those contacts that developed disease, 80% were household contacts. Conclusions: Secondary attack rate was 5.88% and household contacts were the majority to get the disease.